Selective Caries Removal: A Case Report with 21-Year Follow-Up - José Carlos Pettorossi Imparato; Kelly Maria Silva Moreira; Suzana Cavalcanti Monteiro de Oliveira; Sandra Regina Echeverria Pinho da Silva; Daniela Prócida Raggio (Case Reports in Dentistry)
Dental caries remains the most prevalent chronic disease globally, and its management should adhere to the principles of minimal intervention dentistry. This study reports a series of successful cases involving the selective removal of carious tissue in permanent molars, with follow-up periods of up to 21 years. Six permanent molars with severe and deep carious lesions were treated with selective caries removal and restored with high-viscosity glass ionomer cement. Clinical examination revealed that the teeth were free from pain and sensitivity. Follow-up assessments were conducted at 7 and 21 years posttreatment. Treatment success was defined by the absence of clinical and radiographic signs, symptoms of pulp alterations, and lesion arrest. Successful minimally invasive approaches were observed with selective removal of carious tissue and maintenance of pulp vitality for up to 21 years.